Observations from Transforming a Continuing Education programme in the COVID-19 Era and Preparing for the Future. Issue 1 (1st January 2021) - Kawczak, Steven; Fernandez, Anthony; Frampton, Bethany; Mooney, Molly; Nowacki, Amy; Yako, Matthew; Stoller, James K.
ABSTRACT: The COVID-19 pandemic has significantly disrupted and transformed continuing education in the health professions to be reliant on digital learning modalities. This retrospective observational study of a large, international health system's continuing education programme compares educational activities offered, participation, and learning outcomes pre- and intra-pandemic to assess the impact of digitisation advanced because of the pandemic. There was a significant increase in internet-based activities that filled the gap of cancelled or postponed live, in-person activities to keep healthcare professionals up to date in their specialities and prepared to handle the clinical and hospital demands of the pandemic. Compared to live, in-person education, virtual activities were offered in shorter increments, reached a much larger amount of participants, and were equally effective in achieving learning outcomes. Questions remain regarding business model implications to generate adequate revenues to cover costs of virtual education. Additionally, there is a general inadequacy of digital learning environments to coalesce groups and meet social needs. Regardless, the efficiencies and effectiveness of digital modalities will be a primary method of teaching healthcare professionals going forward.